This is Bob Hope [videorecording (DVD)] - Scheinfeld, John (PBS, 2017)
During his eight-decade career, Bob Hope was the only performer to achieve top-rated success in every form of mass entertainment: Vaudeville, Broadway, movies, radio, television, popular song and personal appearances, including hosting the Academy Awards a record 19 times and his annual USO Christmas military tours. Includes film, television, and radio clips; readings of excerpts from Hope's writings; and interviews with prominent entertainment industry figures, family members, and Hope's writers.